2012
DOI: 10.4049/jimmunol.1201097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Staphylococcal Superantigen Elicits a Systemic Inflammatory Disease Mimicking Lupus

Abstract: Chronic nasal and skin colonization with superantigen (SAg)-producing Staphylococcus aureus is well documented in humans. Given that trans-mucosal and trans-cutaneous absorption of SAgs can occur, we determined whether chronic exposure to small amounts of SAg per se could activate autoreactive CD4+ and CD8+ T cells and precipitate any autoimmune disease without further external autoantigenic stimulation. Because HLA class II molecules present SAg more efficiently than do mouse MHC class II molecules, HLA-DQ8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 63 publications
3
41
0
Order By: Relevance
“…Subsequently, 76 µl of 1X PBS was added to this mix to make the volume to 100 µl, the entire content was then loaded into a 7-day release Alzet mini-osmotic pump as per manufacturer’s protocol (Durect Corporation, Cupertino, CA, USA). The pumps were then surgically implanted sub-cutaneously into the back of mice as per standard procedure as described previously (34). The surgical wounds were closed with surgical staples.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 76 µl of 1X PBS was added to this mix to make the volume to 100 µl, the entire content was then loaded into a 7-day release Alzet mini-osmotic pump as per manufacturer’s protocol (Durect Corporation, Cupertino, CA, USA). The pumps were then surgically implanted sub-cutaneously into the back of mice as per standard procedure as described previously (34). The surgical wounds were closed with surgical staples.…”
Section: Methodsmentioning
confidence: 99%
“…Pathological lesions in lungs of transgenic mice, temperature fluctuations, delayed lethal end point later at 96 hour are similar to those in nonhuman primates (NHPs) exposed to lethal doses of SEB 18,111. Low-dose continuous administration of SEB to HLA-DQ8 transgenic mice induces a lupus-like syndrome with multiple organ injury 23. An alternative murine model deploys a “double-hit” strategy with two low doses of SEB using C3H/HeJ mice, an LPS-resistant mouse strain 76.…”
Section: Mouse Models Of Superantigen-induced Shockmentioning
confidence: 66%
“…The cytokines IL-1, TNFα, IFNγ, IL-2, interleukin 6 (IL-6), and chemokines, specifically macrophage chemoattractant protein 1 (MCP-1), are induced early by superantigens in human PBMC. There is also a good correlation of the induction of these cytokines with lethal superantigen-induced shock in murine models 19,21,23,49–52. IL-1 and TNFα also activate other cells, including fibroblasts, epithelial, and endothelial cells, to perpetuate inflammation by inducing cell adhesion molecules and additional mediators from these cells 53.…”
Section: Cellular Response To Superantigensmentioning
confidence: 93%
See 1 more Smart Citation
“…The ALZET ® Osmotic Pumps are small, infusion pumps commonly used to deliver drugs or agents to unrestrained laboratory animals. We have demonstrated that continuous delivery of small amounts of SSAg using such mini-osmotic pumps causes a distinct systemic inflammatory disease in our humanized mouse model (11). In this chapter, we describe the protocol to investigate the systemic effects of chronic exposure to SSAg delivered using miniosmotic pumps.…”
Section: Introductionmentioning
confidence: 94%